The relationship between fitness variables and performance factor in keirin - Bong-Ju Sung; Kwang-Kyu Lee (Korea Institute of Sport Science, 2020)
Purpose The purpose of this study was to examine the relationship between the track records and physical abilities in elite cyclists(keirin). Methods Twenty three elite cyclists were measured height, weight, lower body circumference(thigh, calf, and ankle), basal physical abilities(grip/back muscle strength, 25m sprint, Sargent jump test, Burpee test, shuttle run test), one-repetition maximum(1RM) strength(back squat, bench press, leg curl, power clean, dead-lift, leg press), aerobic capacity(V̇O2max, METs, HRmax), and track records(200m and 500m). Stepwise multiple regression analyses were performed to investigate which physical abilities related to track records. Results A statistically significant relationship was found between 200m track records and 2 variables which were the thigh circumference and 1RM leg press(p<.05). Also, the thigh circumference and 1RM leg press were significantly related to 500m track records(p<.05). Conclusions The results showed that the thigh circumference and maximal strength were associated with the track records in elite cyclists(keirin).